ФЕНОМЕН СОЦІАЛІЗАЦІЇ МОЛОДІ В УМОВАХ ІНФОРМАЦІЙНОГО СУСПІЛЬСТВА - Грінченко, Марина (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті визначено поняття феномену соціалізації у сучасних дослідженнях, розглянуто соціалізацію як процес становлення особистості у суспільстві, проаналізовано особливості інформаційного суспільства, виокремлено особливості сучасної молоді як соціальної групи. Мета дослідження полягає у визначенні різних аспектів та можливих небезпек у процесі соціалізації молоді. Методи дослідження: аналіз, синтез, узагальнення, обробка літературних джерел. Трансформація традиційних механізмів соціалізації та формування таких нових видів соціалізації як медіа соціалізація та кіберсоціалізація призводить до необхідності ґрунтовного вивчення цих процесів та формулювання найбільш прийнятних засобів для сприяння налагодженню цих процесів. В статье определено понятие феномена социализации в современных исследованиях, рассмотрены социализацию как процесс становления личности в обществе, проанализированы особенности информационного общества, выделены особенности современной молодежи как социальной группы. Цель исследования заключается в определении различных аспектов и возможных опасностей в процессе социализации молодежи. Методы исследования: анализ, синтез, обобщение, обработки литературных источников. Трансформация традиционных механизмов социализации и формирования таких новых видов социализации как медиа социализация и киберсоциализация приводит к необходимости тщательного изучения этих процессов и формулировке наиболее приемлемых средств для содействия налаживания этих процессов. The article defines the concept of socialization phenomenon in contemporary studies, considered as the socialization process of identity in society, the peculiarities of the Information Society, singled out the features of today’s youth as a social group. The purpose of the study is to determine the various aspects and potential hazards in the socialization of young people. Methods: analysis, synthesis, synthesis, processing literature. Transforming the traditional mechanisms of socialization and the formation of new types of media as socialization and socialization cyber socialization leads to the need for a thorough study of these processes and formulate the most appropriate means to facilitate the establishment of these processes. Socialization of youth in the information society has many new issues caused by rapid change and transformation in the social environment. Understanding and knowledge of man as the highest value of the information society leads to active development of social personality traits, increased spirituality. However, due to a number of conditions - increasing role of the internet, media, virtual communication, interactivity, destruction of traditional mechanisms of socialization and the formation of new types of socialization as media socialization and cyber socialization leads to the need for a thorough study of these processes and formulate the most appropriate means to promote establishing these processes.